Feeling excited - Holmes, Kirsty (New York, NY KidHaven Publishing, 2019)
Learn about experiencing feelings of excitement, how to connect with them, and how to express them in a healthy way in this nonfiction picture book. Featuring the character Can't-Wait A-Gator, includes tips on dealing understanding and expressing feelings
Education
1 2 13
Keywords: Emotions -- Juvenile literature; Enthusiasm -- Juvenile literature